Directional analysis of drainage network and morphotectonic features in the south-eastern part of Bükk Region - Pecsmány, Péter; HegedűsAndrás; Vágó, János; Németh, Norbert (Hungarian Geographical Bulletin, 2021)
The fracture deformations often result in linear morphological elements (lineaments, valleys) on the surface. In many cases, the direction of the lineaments and valleys can be well followed by the strike of the geological structural elements. Therefore, conclusions can be drawn from these directions for regional tectonic processes. Our work aimed to analyse the relationship between the valley and lineament network and the structural elements in the south-eastern part of Bükk Region. We prepared the theoretical drainage network map and lineament map of the area. The direction of the linear elements was examined separately on the eastern part of South-Eastern Bükk that is built up mainly by Mesozoic limestone and the eastern side of Bükkalja area covered by Neogene and Quaternary sediments. Structural geological surveys were also performed on seven sites to measure the strike of joint sets. These results were compared with the valleys’ direction in the 2 km wide area of the measurement sites. Based on our results, it can be stated that the development of the drainage network was influenced by the geological elements; however, there are local differences in the characteristics of the South-Eastern Bükk and Bükkalja. Our study confirmed that the study of linear morphological elements has great importance in the exploration of geological structural elements.